Challenges and strengthening the role of Pancasila ideology in the reform era through increasing literacy - Ruyadi, Yadi; Hadianto, Daris; Nugraha, Dadi Mulyadi; Praja, Wina Nurhayati; Dahliyana, Asep; Supriyono, Supriyono (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The government has attempted to realize nation and character-building based on Pancasila values through a systemic and planned national education system. However, students' understanding, skills, and actualization of Pancasila values still experience various obstacles, one of which is literacy. Therefore, it is necessary to strengthen the role of the Pancasila ideology through increasing ideological literacy among students. This research aims to uncover challenges and strengthen the role of the Pancasila ideology through increasing literacy. The approach used in this research is qualitative with a literature review method using inductive and descriptive analysis. The research findings found that the challenges of strengthening the role of Pancasila ideology, namely instilling Pancasila values amidst the onslaught of foreign culture, increasing human resources based on Pancasila values, and efforts to maintain its existence. One way to strengthen the role of Pancasila ideology is to increase the literacy skills of Pancasila ideology among students. Increasing literacy in Pancasila ideology can enable students to understand and apply Pancasila values in everyday life. The implication of this research is to increase Pancasila ideology literacy among students and encourage stakeholders or teachers to increase ideological literacy while at the same time instilling Pancasila values among students.